Human Rights and Features of their Protection in Conditions of War: International Legal Standards, Administrative, Constitutional and Criminal Aspects - Yuliia Zaporozhchenko; Yuliia Leheza; Yuliia Volkova; Olena Pushkina; Marat Koval (UIN Sunan Gunung Djati, 2023)
The article is devoted to analysis of constitutional human rights and freedoms under martial law. The main focus is made on the analysis of human rights that may be restricted during martial law. Human rights are divided into absolute ones and relative ones. Absolute rights are determined as rights that cannot be limited under any circumstances. The legal definition of martial law is analyzed. It was found that martial law is the main legal basis for limiting the constitutional rights and freedoms of the person and of the citizen. Grounds for introducing martial law include threats to national security and territorial integrity. Attention is focused on the mechanisms and guarantees aimed at protection of human rights in conditions of martial law. Any restrictions on human rights must be justified, proportionate and necessary to achieve the legitimate goals of security and defense of the state. Affirmation and provision of human rights and freedoms is the main duty of the state. Therefore, during the legal regime of martial law the state cannot cancel its obligation to guarantee human rights. The list of rights which are not subject to restriction even during martial law, are human and citizen’s rights guaranteed by the Constitution. Respect for human rights is a guarantee of state power both at the national and international levels.